1994
DOI: 10.1007/bf00309933
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a nucleomorph hsp70 gene is a common feature of Cryptophyta and Chlorarachniophyta

Abstract: Cryptomonad algae and Chlorarachniophyta are evolutionary chimaeras derived from the engulfment of an eukaryotic phototrophic endosymbiont by a eukaryotic host cell. Although much reduced, the endosymbiont's eukaryotic plasmatic compartment still contains a nucleus, the so-called nucleomorph. These nucleomorphs carry the smallest known eukaryotic genomes. We have characterized the genomes of several cryptomonads and a Chlorarachnion species by means of PFGE (pulsed-field gel electrophoresis). Hybridization stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…As the cryptomonad plastid is clearly derived from a red alga and the chlorarachniophyte plastid from a green alga, their nucleomorphs must have evolved independently from fully-fledged algal nuclei, but they were soon found to share a number of superficial similarities. In all species examined to date, the nucleomorph genome is composed of three small chromosomes, for a total genome size from as little as 373 kbp to over 650 kbp (Rensing et al 1994;McFadden et al 1997a;Gilson & McFadden 1999, 2002Gilson et al 2006;Archibald 2007;Silver et al 2007). In nearly all cases, the rRNA operons are found as subtelomeric repeats on all six chromosome ends, although they face in opposite directions in some species (Gilson & McFadden 1996, 2002Archibald 2007).…”
Section: Nucleomorphsmentioning
confidence: 99%
“…As the cryptomonad plastid is clearly derived from a red alga and the chlorarachniophyte plastid from a green alga, their nucleomorphs must have evolved independently from fully-fledged algal nuclei, but they were soon found to share a number of superficial similarities. In all species examined to date, the nucleomorph genome is composed of three small chromosomes, for a total genome size from as little as 373 kbp to over 650 kbp (Rensing et al 1994;McFadden et al 1997a;Gilson & McFadden 1999, 2002Gilson et al 2006;Archibald 2007;Silver et al 2007). In nearly all cases, the rRNA operons are found as subtelomeric repeats on all six chromosome ends, although they face in opposite directions in some species (Gilson & McFadden 1996, 2002Archibald 2007).…”
Section: Nucleomorphsmentioning
confidence: 99%
“…Preliminary karyotype diversity studies have revealed considerable size variation, with estimated nucleomorph genome sizes ranging from Ϸ450 to 845 kbp in cryptophytes and Ϸ330-610 kbp in chlorarachniophytes (4,(10)(11)(12)(13)(14). The presence of three chromosomes is thus far a universal feature of nucleomorph genomes (3,12,14), as is the existence of subtelomeric rDNA repeats.…”
mentioning
confidence: 99%
“…In those instances studied, nucleomorphs house a densely packed sub genome comprised of three small chromosomes of a total of about 600 kb in the former case and less than 400 kb in the latter McFadden et al 1994a;Rensing et al 1994; with discrete telomers . This corresponds to an estimated number of 200 -300 genes, a figure that has to be related to some 20.000 -40.000 genes per provenance nucleus.…”
Section: The Nucleomorphmentioning
confidence: 98%